The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1101/lm.58603
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Pavlovian Conditioning in Components of the Neural Network Supporting Ciliary Locomotion inHermissenda

Abstract: Pavlovian conditioning in Hermissenda consists of pairing light, the conditioned stimulus (CS) with activation of statocyst hair cells, the unconditioned stimulus (US). Conditioning produces CS-elicited foot shortening and inhibition of light-elicited locomotion, the two conditioned responses (CRs). Conditioning correlates have been identified in the primary sensory neurons (photoreceptors) of the CS pathway, interneurons that receive monosynaptic input from identified photoreceptors, and putative pedal motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Results of the present study are consistent with the hypothesis that US-evoked footshortening and US-reduced locomotion emerge independently (Matzel et al 1990). Previous research has identified intrinsic changes with Pavlovian conditioning in two cell types: photoreceptors and type I interneurons (Crow and Alkon 1980;Crow and Tian 2003b;Farley et al 1990). Neural correlates of Pavlovian conditioning-identified in the neural circuit supporting ciliary locomotion and CS-elicited inhibition of ciliary efferent neuron activity-are now well documented (Crow and Tian 2003b).…”
Section: Circuitry Supporting the Cr Complexsupporting
confidence: 81%
See 1 more Smart Citation
“…Results of the present study are consistent with the hypothesis that US-evoked footshortening and US-reduced locomotion emerge independently (Matzel et al 1990). Previous research has identified intrinsic changes with Pavlovian conditioning in two cell types: photoreceptors and type I interneurons (Crow and Alkon 1980;Crow and Tian 2003b;Farley et al 1990). Neural correlates of Pavlovian conditioning-identified in the neural circuit supporting ciliary locomotion and CS-elicited inhibition of ciliary efferent neuron activity-are now well documented (Crow and Tian 2003b).…”
Section: Circuitry Supporting the Cr Complexsupporting
confidence: 81%
“…Previous research has identified intrinsic changes with Pavlovian conditioning in two cell types: photoreceptors and type I interneurons (Crow and Alkon 1980;Crow and Tian 2003b;Farley et al 1990). Neural correlates of Pavlovian conditioning-identified in the neural circuit supporting ciliary locomotion and CS-elicited inhibition of ciliary efferent neuron activity-are now well documented (Crow and Tian 2003b). However, modification of the neural circuit responsible for CS-elicited foot-shortening is not documented.…”
Section: Circuitry Supporting the Cr Complexmentioning
confidence: 99%
“…In Hermissenda , Pavlovian conditioning produces intrinsic enhanced excitability in identified neurons 18–21 . Associated with conditioning‐dependent enhanced excitability is the phosphorylation of the cytoskeletal‐related protein Csp24 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In Hermissenda, Pavlovian conditioning produces intrinsic enhanced excitability in identified neurons. [18][19][20][21] Associated with conditioning-dependent enhanced excitability is the phosphorylation of the cytoskeletal-related protein Csp24. 22,23 Intermediate-term memory formation produced by one-trial in vitro conditioning is dependent on the expression and phosphorylation of Csp24.…”
Section: Introductionmentioning
confidence: 99%
“…To understand such interacting events, it is necessary to first reduce them to their operant and classical components and then join them again under controlled conditions. Laboratory studies of classical conditioning have successfully interrupted the operant-classical feedback loop such that the behavior of the animal is irrelevant and the two environmental events (the conditioned stimulus, CS, which predicts the unconditioned stimulus, US) can be traced from their sensory afferents to the brain and, finally, to the point where they converge and the learning occurs (e.g., Walters and Byrne 1983;Bao et al 1998;Hawkins et al 1998;Kim et al 1998; Lechner et al 2000a,b;Schafe et al 2001;Medina et al 2002;Paschall and Davis 2002;Ressler et al 2002;Antonov et al 2003;Crow and Tian 2003;Davis et al 2003;Epstein et al 2003;Flynn et al 2003;Mozzachiodi et al 2003;Nader 2003). An analogous convergence point between operant behavior and the unconditioned stimulus (or reinforcer in the operant nomenclature) has recently been described in Aplysia (Nargeot et al 1999a,b;Brembs et al 2002).…”
mentioning
confidence: 99%